IMPLEMENTASI PENDIDIKAN IPS DAN PERILAKU SOSIAL SISWA SMP NEGERI 1 KEBUMEN - Nugroho, Agung (Dinamika, 2015)
Abstract. The success ofthe stateof education in Indonesia, particularly in the formal school curriculum canât be separated from the role of education used by the unit as a reference and guidance in educational activities. Improvements and changes to the curriculum is arequirement in the education world because the life of society, nation and state. In the Indonesian state always changes and curriculum development as the development of society and the influence of globalizations.This study includes qualitative research. The technique of collecting data using questionnaires, interviews, observation and document study. The data analysis technique used in this study is an interactive model of Miles and Huberman developed which consists of data collection, data reduction, data display and conclusion. The results showed that (1) Implementation of appropriate curriculum social studies educationin 2013 by a social studies teacher at state Junior High School 1 Kebumen been executed well even with all the limitations and constraints faced. (2) Implementation of social studies values by grade 7 students of state Junior High School 1 Kebumen been implemented properly. Factors grade 7 social behavior of state Junior High School 1 Kebumen largely influenced by the family environment and school environment. Advice for teachers should increase the understanding and mastery of curriculum related 2013 by attending various training. For the government in order to reform the constraints faced by teachers in implementing the curriculumin 2013.Keywords: Implementation, Social Studies Education, Curriculum 2013, Social BehaviorÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Abstrak. Keberhasilan pendidikan di negara Indonesia khususnya di sekolah formal tidak terlepas dari peranan kurikulum yang digunakan oleh satuan pendidikan sebagai acuan dan pedoman dalam kegiatan pendidikan.Penyempurnaan dan perubahan kurikulum ini merupakan sebuah tuntutan di dunia pendidikan karena kehidupan bermasyarakat, berbangsa dan bernegara.Di Negara Indonesia kurikulum selalu mengalami perubahan dan perkembangan sebagai pengaruh dari perkembangan masyarakat dan globalisasi.Penelitian ini termasuk penelitian kualitatif.Teknik pengumpulan data menggunakan wawancara, observasi dan studi dokumen. Teknik analisis data yang digunakan dalam penelitian ini adalah model interaktif yang dikembangkan Miles dan Huberman yang terdiri dari pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa (1) Implementasi pendidikan IPS sesuai kuriukulm 2013 oleh guru IPS di SMP N 1 meliputi pemahaman dan pengetahuan IPS, perencanaan pembelajaran, pelaksanaan pembelajaran dan evaluasi pembelajaran. (2) Siswa kelas 7 SMP N 1 Kebumen, secara umum siswa telah menerapkan nilai-nilai IPS di sekolah. (3) Faktor perilaku sosial siswa kelas 7 SMP N 1 Kebumen sebagian besar dipengaruhi oleh lingkungan keluarga dan lingkungan sekolah. Saran bagi guru harus meningkatkan pemahaman dan penguasaan terkait kurikulum 2013 dengan mengikuti berbagai pelatihan.Bagi pemerintah agar melakukan pembenahan terhadap kendala-kendala yang dihadapi para pendidik di dalam melaksanakan kurikulum 2013.Kata Kunci: Implementasi, Pendidkan IPS, Kurikulum 2013, Perilaku Sosial